A clinico-social study of functional disabilities among elderly in Palam Village of Delhi - Devendra Kumar; Sanjeev Kumar Rasania; Ranjan Das (Wolters Kluwer Medknow Publications, 2018)
Introduction: Aging, an integral part of living, typically is accompanied by gradual but progressive physiological changes and an increased prevalence of acute and chronic illness and is further compounded by impairment of special sensory functions like vision and hearing and difficulties in performing their routine daily activities seriously affecting the economic, social and psychological aspect of life of older people with disabilities. Objective: To estimate the magnitude of functional disability and its association with various socio-demographic variables among the elderly persons in Palam village of Delhi. Material and Methods: People aged more than 60 years of both sexes and willing to participate were included in this community based cross-sectional study. Barthel ADL index was used for assessment of activities of daily living disability, Snellen's distance vision chart for visual acuity assessment and whisper test was used for hearing assessment. The participants were categorized as functionally disabled if either ADL disability or better eye presenting vision <6/60 or bilateral hearing impairment or a combination of either these were present. Results: The prevalence of functional disability was found to be 23.1% in the study population and was more unmarried/widow/widower group, among illiterates, lower socio-economic class and financially dependent group. Conclusion: Research and studies on elderly in India especially in field of functional disability are less and community dwelling elderly has been neglected at large. Hence it would be useful to estimate the burden of functional disabilities among elderly so that adequate and timely preventive and rehabilitative measures can be taken.